Microwave Assisted Synthesis and Characterization of Titanium oxide, Thorium oxide and Mixed Metal Oxide Nanoparticles for anti bacterial Applications - Santhanaraj, Gomuraj; Alagarsamy , Mathavan (Journal of Neonatal Surgery, 2025)
Metal oxides demonstrate a range of unique properties, such as excellent chemical stability, versatile electrical conductivity, and catalytic abilities. In contrast, mixed metal oxides contain oxygen along with two or more distinct metallic elements. The presence of multiple metals gives mixed metal oxides innovative functionalities and properties that individual metal oxides lack. Titanium oxide and thorium(IV) oxide nanoparticles have attracted significant interest in various scientific and technological fields. This study explores a theoretical approach to synthesizing and characterizing metal oxides, specifically thorium(IV) oxide, titanium oxide, and TTMMO, a mixed metal oxide composed of titanium and thorium. The synthesis of nanoparticles is accomplished using the co-precipitation method with a A microwave reaction system was employed to synthesize nanoparticles, which were then characterized using various analytical techniques including FT-IR, UV-VIS (DRS), FE-SEM, EDAX, AFM, and XRD analysis. XRD analysis confirmed the cubic geometry of ThO2 and the tetragonal structure of TiO2 nanoparticles. Titanium oxide, thorium(IV) oxide, and titanium thorium mixed metal oxides (TTMMO) were evaluated for their antibacterial properties against E. Coli, Bacillus subtilis, Bacillus cereus, Pseudomonas aeruginosa, and Staphylococcus aureus using the disc diffusion technique. Extensive research has been conducted to investigate the exceptional antibacterial activities of these metal oxides and mixed metal oxides